A quasi-experimental comparison of Kolb and Peyton educational approaches on CPR knowledge and performance among nurses - Marzieh Abbasi; Mohsen Taghadosi; Fatemeh Atoof; Reza Hosseiniara (BMC Medical Education)
Abstract Background Many nurses lack adequate knowledge and skills in CPR. Studies have yielded varying results regarding the effectiveness of Kolb and Peyton education methods on nurses’ performance in CPR. Aims The present study aims to compare the effects of education based on Kolb and Peyton methods on nurses’ CPR knowledge and performance. Methods In a quasi-experimental study conducted in 2019, 108 nurses from Kashan’s hospitals meeting the inclusion criteria were selected through convenience sampling. Participants were randomly assigned to three groups: Kolb, Peyton, and a control group. Data collection tools included a demographics form and a research-made questionnaire assessing nurses’ knowledge and performance in CPR. Participants completed the questionnaire before the intervention, as well as one- and six-weeks post-intervention. Data analysis was performed using SPSS 19, employing Chi-square and repeated measures ANOVA (p ≤ 0.05). Results The three groups were homogeneous in terms of demographics, except for age (p = 0.001) and work experience (p = 0.001). While mean knowledge scores in the Kolb and Peyton groups showed statistically significant increases over time (pre-intervention, one-week post-intervention, and six-weeks post-intervention) (p = 0.001 for Kolb, p = 0.000 for Peyton), there was no statistically significant difference in overall knowledge scores between the three groups at any time point (p = 0.06 at six weeks post-intervention, p = 0.32 at one-week post-intervention, and p = 0.36 pre-intervention). Regarding CPR skills, cardiac massage, (p = 0.001 for Kolb, p = 0.001 for Peyton), breathing (p = 0.01 for Kolb, p = 0.001 for Peyton), and defibrillator skills (p = 0.01 for Kolb, p = 0.01 for Peyton) demonstrated statistically significant improvements in both the Kolb and Peyton groups. Furthermore, comparison of these skills among the three groups revealed that the Peyton method was statistically significantly more effective than the Kolb method (p = 0.001 for cardiac massage, p = 0.01 for breathing, and p = 0.01 for defibrillator skills). Conclusion Nurses who received education based on Kolb and Peyton exhibited enhanced knowledge and skills (cardiac massage, breathing, and defibrillator) in CPR. The implementation of these innovative educational methods for CPR training among nurses is recommended.